الحملات الإعلامية و دورها في تحقيق الخدمة الإجتماعية من خلال إذاعة مستغانم نموذجا - قدوري فتيحة; قسوس جميلة (كلية العلوم الإجتماعية, 2022)
ملخص : من خلال الدراسة النظرية و التطبيقية ان ليس هناك إذاعة إلا وتكون معروفة في المجتمع الإعلامي وتكون محظ اهتمام الناس، وبما أن الإذاعة وسيلة إعلامية إتصالية، فإنها تساهم دائما في نشر الحملات الإعلامية وإرشاد وتوجيه وتوعية المواطنين، وهذا عن طريق استخدام جميع أشكال الحملات الإعلامية وإن كان هناك تباين في نسب استخدامه، فالمهم هنا أن الإذاعة تنشر حملات إعلامية متنوعة بهدف استقطاب المشاهدين والمستمعين أيضا، ونشر الوعي الحضاري الإيجابي بين أفراد المجتمع. الكلمات المفتاحية : إذاعة – المجتمع الإعلامي – الحملات الإعلامية – المواطنين- المشاهدين. Summary : Through the theoretical and applied study that there is no radio that does not exist It is well-known in the media community and attracts people’s attention, and since radio is a communicative media, it always contributes to spreading media campaigns and guiding, directing and educating citizens, and this is through the use of all forms of media campaigns. Although there is a discrepancy in the rates of its use, the important thing here is that radio publishes campaigns A variety of media in order to attract viewers and listeners as well, and to spread positive cultural awareness among members of society. Keywords: radio - media community - media campaigns - citizens - viewers
Keywords: radio - media community - media campaigns - citizens - viewers